Icaritin Inhibits Migration and Invasion of Human Ovarian Cancer Cells via the Akt/mTOR Signaling Pathway - Gao, Lvfen; Ouyang, Yuan; Li, Ruobin; Zhang, Xian; Gao, Xuesong; Lin, Shaoqiang; Wang, Xiaoyu (Frontiers in Oncology, 2022)
Ovarian cancer (OC) is the most lethal of all gynecologic malignancies with poor survival rates. Until now, although surgical treatment and chemotherapy had alleviated the disease progress, platinum-based chemoresistance is still a major barrier in the clinical treatment of OC. The search for novel active ingredients for the treatment of drug-resistant OC is urgently needed. Here, we demonstrated that icaritin, the main active ingredient derived from the traditional Chinese herb Epimedium Genus, significantly suppressed the proliferation, migration and invasion of both drug-susceptible and cisplatin (CDDP)-resistant OC cells in vitro. Mechanistically, icaritin at 20 μM significantly inhibited the phosphorylation of Akt and mTOR, as well as decreased the expression of vimentin and increased the expression of E-cadherin. Our data indicate that icaritin, a prenylated flavonoid natural product, could be served as a potential inhibitor of CDDP-resistant OC by the inhibiting Akt/mTOR signaling pathway.